Creation of recombinant Chlamydomonas reinhardtii strains expressing codon optimized vp28 gene from white spot symdrome virus - Huong, Nguyen Minh; Thu, Ha Thi; Hoa, Nguyen Thi; Khang, Dinh Duy; Hong, Dang Diem; Mouradov, Aidyn; Quyen, Dong Van (Academia Journal of Biology, 2018)
White spot syndrome virus (WSSV) is the leading cause of shrimp mortality in farms all over the world. In Vietnam, for the last five to ten years, WSSV has always been among the top causes of diseases and loss in our shrimp aquaculture. VP28 and VP26 are two capsid proteins of WSSV that commonly used as biomarkers for diagnosis and target antigens for vaccine against WSSV. Recombinant VP28 (rVP28) has been studied and expressed in various expression systems including E. coli, yeast and baculovirus. rVP28 expressed in these systems showed effective protection against WSSV in shrimps, though there remains limitation on expression efficiency and safety. Recently, green microalgae Chlamydomonas reinhardtii has been widely used to express pharmaceutical proteins and edible vaccines for aquaculture thanks to its advantages as a safe and efficient host. C. reinhardtii is also used as nutrious natural food for shrimps due to its benefits towards shrimp health and growth. In this study, the codons of vp28 gene was adapted and chemically synthesized, and transformed into the nucleus genome of C. reinhardtii using electroporation. The presence of a codon optimized vp28 gene in C. reinhardtii genome was confirmed by colony PCR and sequencing; and its expression level was examined by RT-PCR. These results proved our success in creating transgenic C. reinhardtiii expressing rVP28 and set the foundation for our future research on edible vaccine against WSSV for shrimp.